2021
DOI: 10.1177/11206721211002442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19-related lockdown on ophthalmic practice in Italy: A report from 39 institutional centers

Abstract: Background/objectives: To compare the number of eye surgical procedures performed in Italy in the 2 months following the beginning of lockdown (study period) because of COVID-19 epidemic with those performed in the two earlier months of the same year (intra-year control) and in the period of 2019 corresponding to the lockdown (inter-year control). Methods: Retrospective analysis of surgical procedures carried out at 39 Academic hospitals. A distinction was made between elective and urgent procedures. Intravitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…vitreoretinal and glaucoma surgery). In fact, this kind of analysis was performed by another recent paper we contributed to [ 6 ]. In the latter, the authors reported a significant reduction in surgical activity during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…vitreoretinal and glaucoma surgery). In fact, this kind of analysis was performed by another recent paper we contributed to [ 6 ]. In the latter, the authors reported a significant reduction in surgical activity during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, at the Policlinico Hospital in Milan, Italy, there was an 81% decrease in intravitreal injections during the national lockdown from March 8 to March 31, 2020 [23]. A retrospective analysis of ophthalmic practices in 39 academic centers in Italy between March 10 and May 9, 2020 revealed an almost 50% decline in intravitreal injections for all indications [24].…”
Section: Real-world Impact On Practice Patternsmentioning
confidence: 98%
“…Clinic restrictions, closure of private clinics, resource shortages, travel restrictions, lack of public transport facilities, and patient concerns were all factors that contributed to the decrease in intravitreal injections [24,25,29]. Younger patients and those with worse visual acuity in the fellow eye were more likely to adhere to anti-VEGF treatment [23,30].…”
Section: Real-world Impact On Practice Patternsmentioning
confidence: 99%
“…23 Also, as recommended by different ophthalmology societies, 12 , 14 we postponed non-urgent surgical interventions. A report from 39 academic ophthalmology centers in Italy, 15 another country severely impacted by the pandemic, compared surgical interventions of the 2-month lockdown period (March 10 to May 9, 2020) to pre-lockdown months (January 10 to March 9, 2020) and corresponding 2 months of 2019 (March 10 to May 9, 2019). Overall, the number of surgeries decreased 68.8% and 69.9%, respectively, with a reduction of 96.2% and 96.4% in the number of elective surgeries and 50.7% and 53.9% in the number of urgent surgeries.…”
Section: Discussionmentioning
confidence: 99%